Trends and outcomes of postpartum haemorrhage, 2003-2011. Issue 1 (December 2015) - Ford, Jane; Patterson, Jillian; Seeho, Sean; Roberts, Christine
Abstract Background While rates of postpartum haemorrhage (PPH) have continued to rise, it is not clear if the association with other morbidity and transfusion has changed over time. This study explores the recent trend in postpartum haemorrhage and whether postpartum haemorrhage is associated with increased transfusions or adverse outcomes over time. Methods Linked birth and hospital data were used to examine ICD-10 AM coded PPH and outcomes in maternal birth admission records, 2003-–2011 in hospitals in New South Wales (NSW), Australia (N = 818, 965 pregnancies). Trends were calculated on the whole population, and among subgroups, and tested using the Cochran Armitage test for trend. Logistic regression models were developed separately for vaginal and caesarean births, and for a maternal morbidity composite indicator (excluding transfusion) and red cell transfusion. Adjusted odds ratios (aOR) for each year relative to 2003 and 95 % confidence intervals (CI) are presented with adjustment for maternal (eg. age, country of birth) and pregnancy factors (eg. parity, interventions, pregnancy complications). Results Overall, there was a significant increase in the PPH rate, from 6.1 % in 2003 to 8.3 % in 2011 (p < 0.0001). Crude rates of postpartum haemorrhage with transfusion increased from 0.75 % (n = 636) to 1.21 % (n = 1145) (p < 0.0001) while crude rates of postpartum haemorrhage with maternal morbidity increased from 0.18 % (n = 149) to 0.23 % (n = 221) (p = 0.02). Having accounted for maternal and pregnancy factors, there were significant overall decreases in the odds ofmorbidity among women with a PPH delivering vaginally (in 2006, 2007 and 2010, aORs were 0.70 (95 % CI 0.52, 0.96) 0.69 (0.51, 0.94) and 0.64 (0.47, 0.87) relative to 2003;p < 0.05), and no significant decrease among women delivered by caesarean section (aOR 0.87 (0.58, 1.29) in 2011;p = 0.37). Among women with a PPH delivering vaginally, there was a trend towards a non-linear increase in the adjusted odds of transfusion by birth year. Compared to women who had vaginal births with PPH in 2003, the adjusted odds for transfusion was between 1.1 and 1.2 fold higher for those with a PPH delivering vaginally in 2007, 2009, 2010 and 2011. However there was no significant trend amongst caesarean births (aOR 0.84 (0.66, 1.06) in 2011;p = 0.29). Conclusions PPH has become more frequent, however this has not been associated with a clear pattern of increased severe maternal morbidity. This suggests that the increase in PPH may represent fewer severe haemorrhages, better management of severe haemorrhage or better recording of PPH. The increase in transfusions following vaginal births with PPH warrants further investigation.